Institutional Assessment of Sindh Technical Education and Vocational Training Authority - World Bank (Washington, DC, 2014)
Providing quality training that leads young people to jobs is critical for the economic and social development of the Province of Sindh, Pakistan. This working paper assesses the strengths and weaknesses of the Sindh Technical Education and Vocational Training Authority (STEVTA) as a provincial apex body in Technical Education and Vocational Training (TVET). The recent establishment of STEVTA was a major step to reduce fragmentation of training policies and programs. The paper assesses the Authority's legal foundation, governance, management, organization, human resources, financial resources and management, and networking with external organizations. The institutional assessment finds that Government of Sindh and STEVTA need to: (i) strengthen its governance by establishing a clearer reporting structure for the management of the authority's director, and by increasing the involvement of the private sector in the board, (ii) enhance its institutional capacity through hiring of teachers in its institutions based upon increased funding and a sustainable HR rationalization plan for the system that is coordinated with planned physical investments in institutions, and (iii) build strong operational capacity by establishing rules of business and management information systems, and drafting a strategic plan. Lastly, to fully achieve its mandate, continued and consistent governmental support is essential to give STEVTA stability and funding to fulfill its mandate: employment through skills.